The Effect of Integrated Chemoentrepreneurship-Based Malapat Village Ethnochemistry on Students' Entrepreneurial Interests - Tamrin Taher; Nindi Arista Abdurrazak; Marlina Ruslan (Universitas Negeri Gorontalo, 2025)
One of the reasons why high school and vocational school graduates are the highest contributors to the open unemployment rate is the lack of job opportunities that match their level of education and the lack of skills for alternative jobs, for example entrepreneurship. This research aims to ; (1) Integrate approach chemoentrepreneurship with Village ethnochemistry Malapat in chemistry learning , (2) Knowing what is what there is difference interest entrepreneurship student after taught with the integrated chemoentrepreneurship approach of ethnochemistry in Malapat Village . This study uses a preexperimental design method through one group pretest-post-test design . The subjects of the study were 24 students of class XI of SMA Negeri 25 Halmahera Selatan. Data collection through an entrepreneurial interest instrument consisting of 17 items. Data analysis using descriptive statistics ( paired test ). The findings of the study indicate that the integrated chemoentrepreneurship approach of ethnochemistry in Malapat Village can be implemented using the Project Based Learning model with the following steps; 1) Identifying and determining a local culture-based product manufacturing project, 2) Planning the product manufacturing steps including analysis of materials and costs required, 3) Compile timetable product making, 4) Monitoring the implementation of product making, 5) Making reports and business plans for the products produced, 6) evaluating the products produced. The paired test showed a significance of pre-test and post-test of 0.026 which indicated that there was a difference in students' interest in entrepreneurship before and after participating in learning